2020
DOI: 10.21203/rs.2.24555/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Night sleep duration and risk of each lipid profile abnormality in a Chinese population: a prospective cohort study

Abstract: Background To explore the associations between sleep duration and abnormalities in serum lipid levels in a Chinese population. Methods A prospective study was conducted with 34,260 participants from the general Chinese population. Sleep duration was categorized as ≤5, 6, 7, 8 or ≥9 h. Each lipid profile abnormality was defined according to the Chinese Guidelines for the Prevention and Treatment of Dyslipidemia in Adults (2016). The Cox proportional hazards model was used to assess the association between sleep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…The present study did not find any association between TST and LDL-C. A previous study, however, reported thatcompared to 7 hours -a sleep duration of 8, but not 9, hours was associated with abnormal (high) LDL-C. 13 Several reasons may explain these contradictory results. First, whereas the above study used self-reported sleep duration, our present study relied on objective measurement of TST.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The present study did not find any association between TST and LDL-C. A previous study, however, reported thatcompared to 7 hours -a sleep duration of 8, but not 9, hours was associated with abnormal (high) LDL-C. 13 Several reasons may explain these contradictory results. First, whereas the above study used self-reported sleep duration, our present study relied on objective measurement of TST.…”
Section: Discussioncontrasting
confidence: 87%
“…Indeed, most previous studies investigating the association between sleep duration and cholesterol levels used self-reported sleep measures. 7,[11][12][13][14] Collection of objective sleep data is therefore critical in reducing such bias. A recent study validated the use of a consumer wearable device for global sleep measures in a naturalistic environment, indicating its suitability for use in epidemiologic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Existed evidence have revealed the associations of sleep duration with simple lipid and glucose metabolism indicators, such as WC [32], HDL-C [33], and TG [34,35]. However, the conclusions were, to a large extent, controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the current study aims to address the following gaps in the literature. First, though some empirical studies have suggested the extreme sleep duration and poor sleep quality were associated with higher risks of cognitive impairment among Chinese older adults, most of them were based on a small sample from regional surveys (such as Beijing, Guangzhou, or Hebei province, Zhejiang Province) at middle and young older ages [15,52,53]. Using a nationally representative panel dataset from mainland China from 2008 to 2011, we aim to investigate the associations between sleep duration and quality and cognitive function, between FVI and cognitive function, and how sleep duration and quality and FVI are jointly associated with cognitive function.…”
Section: Introductionmentioning
confidence: 99%